TINJAUAN YURIDIS KEDUDUKAN DAN HAK ANAK ANGKAT TERHADAP HARTA WARISAN PENINGGALAN ORANGTUA ANGKAT BERDASARKAN PUTUSAN PENGADILAN NEGERI TEBING TINGGI NO. 23/Pdt.Bth/2021/PN.Tbt - Cindy Haryadmo, Veronika; Sembiring, Rosnidar; Kaban, Maria (Penerbit Lafadz Jaya, 2025)
Adoption is an effort to attract other children, whether related by blood or not, to the family of the person who is adopting the child. Adoption must be carried out according to customs and law. This research is normative legal research. The nature of the research is descriptive analysis. The sources of research data are primary data, secondary data, and tertiary data. Then, the data was collected using literature study techniques and field studies with data collection tools in the form of interviews. Furthermore, the data was analyzed using qualitative analysis methods. The results of this study discuss adoption and the legal status of adopted children. In Batak customs, adoption resembles Staatsblad 1917 No. 129, where adopted children are considered biological children and sever ties with biological parents, while Law No. 35 of 2014 does not sever these blood ties. In Islamic law, adopted children do not inherit directly but can receive inheritance through a will. Batak customs initially prioritized boys, but now girls can also be adopted and inherit property through jurisprudence. Based on Staatsblad 1917 No. 129, adopted children have inheritance rights as part of the adopted family. Decision No. 23/Pdt.Bth/2021/PN.Tbt confirms that adopted children have the right to inheritance without harming biological heirs, as long as the adoption is carried out through the court.